Invasive Bacterial and Fungal Infections After Pediatric Cardiac Surgery: A Single-center Experience. Issue 4 (April 2021) - Tönz, Gian Maria; Kadner, Alexander; Pfammatter, Jean-Pierre; Agyeman, Philipp Kwame Abayie
Abstract : Background: Discrimination of infectious and noninfectious complications in children with inflammatory signs after cardiac surgery is challenging. Given the low prevalence of infectious complications after heart surgery, there might be a risk of excessive antibiotic usage. We performed this study to determine the rate of invasive bacterial or fungal infections in children after cardiac surgery at our institution and to evaluate our postoperative management. Methods: This single-center retrospective observational cohort study included children 16 years of age or younger who underwent cardiac surgery at our institution between January 2012 and December 2015. Results: We analyzed 395 surgical procedures. Thirty-five postoperative invasive bacterial or fungal infections were detected in 29 episodes (7%, 0.42 per 100 admission days). Among bacterial infections, the most common infection sites were bacteremia and pneumonia, accounting for 37% (13/35) and 23% (8/35) of infections respectively. The rate of postoperative infections was associated with surgical complexity score and length of postoperative pediatric intensive care unit (PICU) stay. In 154 (43%) of 357 episodes without microbiologically documented infection, uninterrupted postoperative antibiotic administration was continued for more than 3 days and in 80 (22%) for more than 5 days. Conclusions: The rate of postoperative bacterial or fungal infection at our institution is comparable to current literature. High surgical complexity score and prolonged length of PICU stay were risk factors for bacterial or fungal infections in this patient population.